Resistome-based surveillance identifies ESKAPE pathogens as the predominant gram-negative organisms circulating in veterinary hospitals - Zendri, Flavia; Isgren, Cajsa M.; Devaney, Jane; Schmidt, Vanessa; Rankin, Rachel; Timofte, Dorina (Frontiers in Microbiology, 2023)
Introduction: Healthcare-associated infections (HCAIs) associated with extended-spectrum cephalosporin resistant gram-negative (ESC-R GN) bacteria are an emerging concern in veterinary hospitals, especially in companion animal intensive care units (ICUs). Methods: To understand the molecular epidemiology of ESC-R GN isolates in two veterinary hospitals (equine and small animal), a six-month pilot study was performed during which faecal and environmental samples were obtained twice from selected patients, upon ICU admission and after 48 hours of hospitalisation. In total, 295 ESC-R GNs were analysed using the Acuitas Resistome® Test (OpGen, Maryland, US) a PCR-based assay screening for 50 antimicrobial resistance gene families encoding production of extended-spectrum beta-lactamase (ESBLs), TEM/SHV/OXA or AmpC beta-lactamases and carbapenemases. Combining organism identification and antimicrobial susceptibility data to genotyping results, unique ‘Acuitas Profiles’ were generated that can be used for fast typing the isolates and tracking transmission events. Results: ESKAPE GN pathogens were the most prevalent ESC-R GN isolates circulating in both the small animal and equine hospitals, consisting of Enterobacter cloacae complex (21.7%), Pseudomonas aeruginosa (20%), Klebsiella pneumoniae (15.9%), and Acinetobacter baumannii complex (13.6%) followed by Escherichia coli (12.2%), most harboring a combination of genes encoding for beta-lactamases and ESBLs. Some ESKAPE genotypes showed likely intra-hospital transmission, including E. cloacae (two genotypes, one carrying SHV4, SHV5 and TEM7 and the other TEM1, TEM3 and TEM7 enzymes) in the equine and K. pneumoniae (SHV1, SHV5 and DHA1- positive) in the small animal ICUs, respectively. Furthermore, P. aeruginosa (carrying OXA-50), A. baumannii complex (OXA-51) and E. coli (CTX-M-1) genotypes were isolated across both hospitals, suggesting possible transfer mediated via movement of staff and students. Importantly, isolates carrying transmissible resistance to last resort antimicrobials (i.e. carbapenems) were identified within the hospital environments, consisting of three environmental Acinetobacter spp. harboring blaOXA-23 and one clinical E. coli with blaOXA-48. Conclusion: We describe widespread occurrence of ESKAPE gram-negative organisms in veterinary ICU patients and hospital environments. Findings from this project provide baseline data on the epidemiology of ESKAPE pathogens in veterinary settings, which can inform infection control policies to aid in patient management and prevent transmission of nosocomial infections associated with these pathogens.